Nurses’ Caring Behaviors for Dying Patients in Southern Thailand - Prompahakul, Chuleeporn; Nilmanat, Kittikorn; Kongsuwan, Waraporn (Nurse Media Journal of Nursing, 2011)
Background: Nowadays, the end-of-life care becomes an indicator of the quality of care in a hospital. However, current nursing standards and quality of care related to the end of life do not meet the desired expectations of both dying patients and their families. Therefore, caring behaviors of nurses need to be described.Purpose: The purpose of this descriptive research was to describe the level of nurses’ caring behaviors for dying patients in southern Thailand. Method: Proportionate stratified random sampling was used to select 360 registered nurses who had been working in general hospitals and regional/university hospitals in southern Thailand for at least one year. Instruments used in the study included the Demographic Data Questionnaire (DDQ) and the Nurse’s Caring Behavior for Dying Patients Questionnaire (NCBDQ). The questionnaires were content validated by three experts. The reliability of the NCBDQ was tested with 30 nurses yielding a Cronbach’s alpha coefficient of .97. The data were analyzed by using frequency, percentage, mean and standard deviation.Results: The level of nurses’ caring behaviors for dying patients was high (M = 2.12, SD = .43). The five dimensions of the nurses' caring behaviors including compassion, confidence, conscience, commitment and comportment were also at a high level. However, the competence dimension was at a moderate level (M = 1.82, SD = .51). Conclusion: The results of this study indicated that nurses perceived themselves as having a moderate level of competency in taking care of dying patients. Therefore, educational intervention on enhancing nurses’ competency for end of life care is recommended. In addition, factors relating to nurses’ caring behavior for dying patients should be further explored.Keywords: caring behaviors, dying patients, nurses, southern Thailand